Knowledge, Attitude, Practice and Stigma Related to COVID-19: A Nigerian Perspective (Nigerian Journal of Physiological Sciences, 2021)
Pandemics have claimed an estimated 414 million lives from 165 AD to present, with COVID-19 pandemic killing close to 2 million people. The best counter for pandemics has been the use of vaccines, but before it is widely available, the best strategy is to avoid being infected. COVID-19 pandemic was met by behaviours and attitudes ranging from unbelief to fear of dying and stigmatisation of those who have contracted the virus or recovered from the disease. This study aimed to investigate the knowledge, attitudes, practices (KAP), fear and stigma of the populace towards COVID-19 from state to state. This research was a cross-sectional study carried out from April to October 2020. Data was obtained through a structured questionnaire distributed to 650 individuals. Respondents who participated were 591 (males n= 335 and females n= 256) and aged 18-60 years (mean age 30.25 ± 10.45 years, range 18-60) drawn from five states in the north-central region of Nigeria. The results show that 98.3% of participants believe that COVID-19 disease exists. Still, not everyone wears face masks, avoid crowded places, practice social distancing or follow the WHO-hand-washing technique as measures to curb the spread of the disease. Only 60.5% of the participants believe that lockdown is an effective measure to reduce transmission risk. 55.6% will stigmatise those who just recovered from the disease, 75.3% are afraid to visit high-risk areas as part of the protective measures, but only about 12% believe that every infected person will die. More males (28.3%) than females (17.6%) believe that taking herbs can cure the disease (P